Risiko Investasi dalam Pembangunan Jalan Tol di Indonesia - Rudy Hermawan Karsaman (Journal of Regional and City Planning, 2007)
In  accordance  with an  effort  to  increase  economic  development  for  the welfare  of  the  society,  the  government  of  Republic  of  Indonesia   plan  to develop infrastructures,  including  toll  road,  in  a  big  scale.  On  the contrary to the high investment potential, there are some risks arise and have to be faced by government and investors. These risks has to be taken into account in investment cal culation as a whole and managed very well since the beginning so that it can be anticipated as early as possible. Risk management  is  a  well  and   systematic  approach  to  manage  these  risk, started from risk identification and responses. In toll business, t here are so many risk have to be faced in every stage, from planning, construction until operation and maintenance stages, with the magnitude of very small to very big and probability occurrence from very rare to always happen. In  this  case,  attitude  toward  this  risk  are  accept,  mitigate,  transfer  to other party, or avoid at all. Regional/Local government could participate in  toll  road  development,  either  as  part  of  regulator  or  investor,  this might slightly change risk implication.